Second Five Year Plan Mysore - Planning Commission (Planning Commission)
Due to acute shortages of food., cotton and jute brought about by the Second World War and the partition of the country the First Five-Year Plan laid special emphasis on and mobilised all resources towards removing these shortages. Therefore considerable sums of money were allotted in the First Plan for stepping up production of foodgrains and cotton.
Mysore